HOW TO ADJUST THE QUARTER WAVE LINE ON THE HALF-WAVE OPERATING MODE - Patsiuk V.I (Problems of the Regional Energetics)
On the basis of the equations of the established mode the closed formulas for distribution of voltage, currents and active capacity along a non-uniform line with the concentrated elements are received. Inclusion of throttles and condenser batteries in a quarter wave line is examined with the purpose of giving to it of properties half-wave.